Revealing microstructure evolution and mechanical properties of Al/Cu joints during high-speed friction stir welding - Lisheng Zuo; Youjian Han; Wendeng Shao; Xingquan Zhang; Dunwen Zuo (Journal of Materials Research and Technology)
Friction stir welding provides several advantages, including relatively low welding temperature, no thermal crack, and excellent joint performance. However, due to the narrow process window, the research on the friction stir welding of aluminum and copper is mainly focused on the lower welding speed range, which greatly affects the welding efficiency. Addressing the challenge of increasing welding speed and optimizing process parameters has become an urgent priority. In addition, the dynamic recrystallization behavior during high-speed Al–Cu friction stir welding is complex, and the microstructure evolution is still unclear. In order to clarify these issues, the high-speed friction stir welding (HSFSW) experiment was carried out, and the influence of rotation speeds on microstructure evolution and mechanical properties of joints at high welding speed was investigated. The results show that when welding speed is fixed at 400 mm/min and rotational speeds are in the range of 2000∼2500r/min, the joints can be obtained with good surface morphology and no internal defects. The ultimate tensile strength of specimen is 191 MPa at the process parameters of 2250r/min-400 mm/min, which is 77% of the strength of copper base material. As the rotation speed increases, a thick intermetallic compounds layer appears inside the joint. Due to the influence of thermal cycle and stirring of pin, the nugget zone undergoes a large amount of recrystallization behaviors and forms fine equiaxed grains, which is conducive to refined crystalline strengthening, thus improving mechanical properties of joints.